Advancing Environmental Protection: The Impact of Technological Innovations on Monitoring and Preventing Environmental Violations - Rezi, Rezi; Rahayu, Istiyawati; Mansor Manan, Mohamed (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Environmental violations committed by humans are one of the important causes of climate change, such as greenhouse gas emissions, deforestation, and biodiversity loss. Conventional supervision efforts to prevent environmental violations are quite difficult to do because of limited human resources, large areas and difficult access and the time to respond to violations is slow. This article uses normative research methods and is based on secondary data, the results of which are presented descriptively and analytically. This article will focus on exploring technological innovations that can be used to monitor and prevent environmental pollution, as well as how such technologies can effectively support environmental law enforcement.